On the solutions of difference equations of the Volterra type - Adiguzel, Hakan (Tubitak Scientific & Technological Research Council Turkey, 2025)
In this paper, we conduct a thorough analysis of the qualitative behavior of solutions to three different types of difference equations of the Volterra type. Utilizing the principles of discrete calculus and various well-known inequalities, we have presented our findings. To conclude our theoretical findings, we provide several examples that illustrate full alignment with the findings.
Keywords: Oscillation; nonoscillation; positive solutions; asymptotic behavior